2015
DOI: 10.1038/jp.2015.124
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity, lung function and fitness assessment after bronchopulmonary dysplasia

Abstract: More frequent wheezing and reduced lung function persist into school age after BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…A total of 6042 article titles were identified of which 183 full articles were screened for inclusion. Nineteen met the inclusion criteria (Figure ) . For the three studies that overlapped data were kindly supplied by the authors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 6042 article titles were identified of which 183 full articles were screened for inclusion. Nineteen met the inclusion criteria (Figure ) . For the three studies that overlapped data were kindly supplied by the authors .…”
Section: Resultsmentioning
confidence: 99%
“…Medians and IQRs or ranges were converted to means and standard deviations for three studies . Mean and 95% CI were converted to mean and standard deviation for one study …”
Section: Resultsmentioning
confidence: 99%
“…The proportion of children with a reduced FEV 1 < 80% were preterm BPD group (68%), preterm no BPD (24%) and healthy controls (15%, P < 0.001). There was no significant difference between preterm no BPD and healthy controls (24% vs. 15%, P = 0.35) …”
Section: Lung Function Outcomesmentioning
confidence: 75%
“…Using the reference equation VO 2 max = 4.19 (95% CI, 1.12‐7.17) + 0.025 (95% CI, 0.018‐0.031) distance, 26 the difference in exercise capacity of 159 m would equate to a VO 2 max difference of approximately 8.2 mL min −1 kg −1 . In addition, others have shown that measures of exercise capacity, rather than VO 2 max, are also reduced in prematurely born individuals 28 . In one study, 178 preterm and 218 full‐term were monitored annually between eight and 18 years of age.…”
Section: Discussionmentioning
confidence: 99%